The Effect of Pillbox Use on Medication Adherence Among Elderly Patients: A Randomized Controlled Trial - Ashraf Mehdinia; Marzieh Loripoor; Mahlagha Dehghan; Shahin Heidari (Disease and Diagnosis, 2020)
Background: Poor medication adherence may cause unfortunate consequences such as disease progression and even death, particularly in older adults. This study aimed to evaluate the effect of pillbox use on medication adherence among older adults with cardiovascular diseases. Materials and Methods: This study was conducted as a two-group randomized controlled trial in a clinic in Kerman, Iran in 2017. Participants included seventy patients who were randomly allocated to either a control or an intervention group. The patients in the intervention group were verbally educated to manage their medications using a pillbox for four consecutive weeks while their counterparts received their medications without the use of any drug reminders. Results: The mean score of all participants’ medication adherence was 4.02±2.19 at the beginning of the study. Medication adherence significantly improved in the intervention group during the study (P<0.001) while it remained poor in the control group (P>0.99). Finally, medication adherence was significantly better in the intervention group compared to the control group at the end of the study (P=0.001). Conclusion: In general, pillbox use can promote medication adherence in older adults with cardiovascular diseases thus it is recommended for improving medication adherence and minimizing the consequences of non-adherence.